Structural, Morphological and Optical Properties of Mg: ZnS Nanoparticle for Future Contribution in Different Biological Uses - Jinan A. Abd (Journal of Global Pharma Technology, 2017)
The wet chemical co- precipitation technique has been used to prepare magnesium doped zinc sulfide nanocrystal powder at room temperature for future contribution in technological and biological applications. The crystal structural, morphology, optical properties, and the emission spectrum of the powder were characterized by x-ray diffraction (XRD), atomic force microscopy (AFM), UV-VIS spectrophotometer, and photoluminescence (PL) spectra. The analysis of XRD diffraction indicated that the powder had cubic zincblende structure and the calculated value of crystallite size was (15.9 nm) for the preferential orientation diffraction peak (111). The calculated energy gap of the Mg:ZnS nanoparticles was ( 3.87 eV) from absorbance spectrum. The PL spectrum of the nanoparticle confirmed two peaks located on (367 nm) and (485 nm).